METODE PELAKSANAAN DAN EVALUASI PERBAIKAN JALAN BETON DENGAN INJEKSI SEMEN, COR DI TEMPAT DAN BETON PRACETAK - A. Tatang Dachlan (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
The road concrete pavements for high volume traffic load in Indonesia are mostly faced to the unstable base layer and eroded drainage factor then fallout deterioration such as irregular cracks, pumping, spalling ad faulting. The effect of those factors may appear propagation cracks or depression that needs demolition of whole concrete or apart of panel for repairing. The process requires a fast way repair, without hampering the flow of traffic. The defect must be identified causes and conditions carefully by means of visual condition assessment and mapping, deflection test with Falling Weigt Deflectometer (FWD), and sampling with core drill prior to repair. Based on the trials of concrete pavement suffers by pumping and depression, handling of the injected liquid cement ixed with a certain additive material, may reduce differential deflection so the slab is stable. Another repairs is the panel was removed and replaced with cast-in-place concrete using concrete mix that was given an additive to accelerate the hardening reaches 80% design strength, and within 3x24 hours can be immediately opened to traffic. The broken slab may also directtly be repalced using precast concrete with an appropriate dimension, the process is relatively fast then the traffic may immediately be opened. Monitoring result in improvements at the end of the first year, in the joint after grouting based on deflection criteria showed no indication of voids with a deflection of less than 0.05 mm (2 mils), and load transfer efficiency of more than 60%. This perform is usefull on preservation system of concrete pavement in Indonesia. Key words : pavement repairs, concrete pavement, segment cast in place, cement injection, precast concrete slab.